49 The responsiveness of multifactorial outcome measures for those with chronic ankle instability. (12th October 2015) - McKeon, PO; Wikstrom, EA
Abstract : Background: Chronic ankle instability (CAI) is a multifactorial condition marked by mechanical insufficiencies, sensorimotor deficits, and functional limitations. Clinician- and patient-oriented measures have been developed to capture these factors, but their responsiveness has not been examined concurrently. Objective: To establish the concurrent responsiveness of 4 clinician- and patient-oriented outcome measures in patients with CAI. Design: Reliability study. Setting: Research laboratory. Participants: Seventy-nine patients with self-reported CAI had their self-reported better limb assessed across a 2-week interval. CAI was defined as at least two episodes of "giving way" within the past 3 months; scoring ≤90% on the Foot and Ankle Ability Measure (FAAM), and scoring ≤80% on the FAAM-Sport. Interventions: Each participant underwent two separate functional assessments of the weight bearing lunge test (WBLT), the single limb balance test (SLBT), and completed the Foot and Ankle Ability Measure (FAAM), separated by two weeks. The FAAM included the activities of daily living (FAAM-ADL) and sport activities (FAAM-Sport) subscales. Main outcome measures: The means of 3 trials of the WBLT (cm) and the SLBT (number of errors during 20 s) were used for the analysis of clinician-oriented outcomes. The FAAM-ADL and FAAM-Sport scores were calculated as a percentage of the total score for each scale as patient-oriented outcomes. Reliability estimates were calculated for clinician-oriented outcomes (ICC(2, 3) ) and patient-oriented outcomes (Cronbach's α). From the reliability estimates, the minimum detectable change (MDC) was calculated for each measure. Results: The clinician-oriented measures demonstrated high reliability with relatively low measurement error (WBLT ICC(2, 3) = 0.98, MDC = 0.75 cm; SLBT ICC(2, 3) = 0.86, MDC = 1 error)  as did the patient-oriented measures (FAAM-ADL α = 0.91, MDC = 4.8%; FAAM-Sport α = 0.90, MDC = 7.6%). Conclusion: The concurrent responsiveness of these clinician- and patient-oriented outcomes can now be interpreted in the context of measurement error associated with changes over time related to improvements from rehabilitation or deteriorations due to recurrent injury.